Permanent urethral catheter - a good servant, but bad master: Guidelines for prevention, diagnosis, and treatment of catheter-associated urinary tract infections - Šámal, Vladimír; Krhut, Jan; Zachoval, Roman; Matoušková, Michaela; Ák, Miloš Bro (Casopis lekaru ceskych, 2023)
Catheter-associated urinary tract infections (CAUTI) are among the most common healthcare-associated infections, which increase morbidity, mortality, prolong the length of hospitalization and have a significant impact on the cost of treatment. The most efficient preventive method is removing catheters as soon as possible and avoid unnecessary catheterizations. Treatment of asymptomatic bacteriuria is not recommended. In cases of serious CAUTI, vigorous antibiotic therapy covering multidrug-resistant uropathogens should be initiated. These recommendations are intended for all medical specialties to improve the care of patients with indwelling catheters in the prevention, diagnosis, and treatment of CAUTI in primary care and subsequent long-term care.
Keywords: catheter-associated urinary tract infections; Urinary Catheters; urinary tract infection; Urinary Tract Infections; Humans; močové katétry; infekce močového ústrojí; Hospitalization; lidé; dysfunction of lower urinary tract; urinary infection; permanent urethral catheter; hospitalizace; intermittent catheterization